Study the effect ofmagnet icfield on the properties of silver thin films prepared by dc sputtering - A .Khadayeir, Abdulhussain; Rajh .Taly, shimaa (Al-Qadisiyah Journal of Pure Science, 2018)
Silver thin films by Dc sputtering method on glass substrate for different deposition times (10,30 and 60)sechave been prepared and deposited . The thicknesses of Ag thin films measured by using an optical interferometer method employing He-Ne laser (632.8)nm wavelength . Thin films thicknesses without magnetic field was (84,89 and 94)nm while with magnetic field was(127,269 and 290)nm for same times. Structure and Optical properties have been analyzed by using XRD and UV-V spectroscopy and XRD analysis show that thin films were face centered cubic structure. Absorption and Transmittance spectra of silver thin films were recorded in the wavelength range between 300nm to1100nm . High absorption coefficient of silver thin films determined from the analysis of absorption spectra . The electrical properties show the resistivity inversely proportional with silver thin films thickness.